2010
DOI: 10.2166/wst.2010.415
|View full text |Cite
|
Sign up to set email alerts
|

Geosmin and 2-methylisoborneol adsorption on super-powdered activated carbon in the presence of natural organic matter

Abstract: Geosmin and 2-methylisoborneol (2-MIB) are naturally occurring compounds responsible for musty-earthy-odors in surface water supplies. They are a severe problem confronting utilities worldwide. Adsorption by powdered activated carbon (PAC) is a widely used process to control this problem, but it has low efficiency, which engenders large budget spending for utilities services. Super-powdered activated carbon (S-PAC) is activated carbon with much finer particles than those of PAC. Experiments on geosmin and 2-MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
(8 reference statements)
2
7
0
2
Order By: Relevance
“…The pore size distribution of activated carbon particles is an important parameter related to their equilibrium adsorption capacity. It has been reported previously that the change in carbon particle size by micro-milling does not result in any substantial change in pore size distribution (Ando et al, 2010;Matsui et al, 2015). The results of our study also confirmed that the pore size distributions were similar for different-size particles (PAC, SPAC, and SSPAC) with the same age, although experimental errors were apparent in the data for oneyear-old carbon ( Fig.…”
Section: Pore Size Distributionssupporting
confidence: 91%
See 3 more Smart Citations
“…The pore size distribution of activated carbon particles is an important parameter related to their equilibrium adsorption capacity. It has been reported previously that the change in carbon particle size by micro-milling does not result in any substantial change in pore size distribution (Ando et al, 2010;Matsui et al, 2015). The results of our study also confirmed that the pore size distributions were similar for different-size particles (PAC, SPAC, and SSPAC) with the same age, although experimental errors were apparent in the data for oneyear-old carbon ( Fig.…”
Section: Pore Size Distributionssupporting
confidence: 91%
“…Equilibrium adsorption capacities in our study also increased with decreasing carbon particle size. A similar phenomenon has been reported for virgin PAC and its SPAC (Matsui et al, 2010;Matsui et al, 2012) as well as for one-year-old used GAC and its PAC (Hu et al, 2015;Knappe et al, 1999).…”
Section: Mib Adsorption Capacitysupporting
confidence: 77%
See 2 more Smart Citations
“…Toz aktif karbon (TAK), içme suyu arıtımında sıklıkla tercih edilen bir fizikokimyasal arıtım yöntemidir [72]. Toz aktif karbon ile Geosmin ve 2-MIB gibi tat ve koku oluşturan bileşiklerin giderilmesinin incelendiği birçok çalışmanın [11], [41], [73], [74] Li [97]'nin yürüttüğü bir başka çalışmada da, Ti/RuO2-Pt anot ile NaCl kullanımıyla Geosmin konsantrasyonunun 600 ng/L'den 6 ng/L'ye düştüğü görülmüştür.…”
Section: Toz Aktif Karbonunclassified